Relationship between military expenditure and economic development in the United States of America, France, India and China - Khalid, Masoud Ali (2014)
This study investigated the relationship between government military expenditure and economic development in four countries namely, United States of America, France, China, and India over the period from 1970-2011. The specific objectives of this study are: (i) to determine the impact of military expenditure on economic growth, and (ii) to examine the determinants of military spending in the four countries. To achieve the two objectives in this study the researcher used Autoregressive distributed lag (ARDL) bounds test approach developed by Pesaran et al. (2001) on the new macroeconomic model by Romer and Taylor (2000), and Wagner’s Law model by Peacock and Wiseman (1961). For the independent variables, several macroeconomic variables were used such as government non-military expenditure, real interest rate, Gross Domestic Product Growth, population and exports, while for the dependent variables, Gross Domestic Product and government military expenditure were employed. The results for the first objective reveal that, in the short and long-run, the relationship between government military expenditure and economic growth is significant and negative in the case of the USA, while for France and China this relationship is significant and positive in the short-run . In contrast, this relationship is inconclusive in the long-run for both counties. Additionally, the correlations between these two variables are also inconclusive in the case of India. The results for the second objective show that, population and export are the negative factors to determine military expenditure for the USA in the short-run, and statistically significant, but inconclusive in the long-run. Moreover, in the case of France, the result indicates that, Gross Domestic Product Growth plays a negative and significant role to determine the government’s military spending in both periods, while export plays a positive and significant role in military spending in the short-run, but it is insignificant in the long-run. Furthermore, the result for China indicates that, in the long-run, export is positive and significant and it is the main factor determining the Chinese military expenditure, while this result is in contrast to the short-term, and it is an inconclusive result. Population is an important determinant of military spending in the short-run, and positive and significant for the Chinese military sector. Furthermore, population and exports are extremely important factors in determining the Indian military spending in both periods.